Self‐Assembly of Cyclohelicate [M3L3] Triangles Over [M4L4] Squares, Despite Near‐Linear Bis‐terdentate L and Octahedral M. Issue 57 (23rd August 2017) - Hogue, Ross W.; Dhers, Sébastien; Hellyer, Ryan M.; Luo, Jingwei; Hanan, Garry S.; Larsen, David S.; Garden, Anna L.; Brooker, Sally
Abstract: Invited for the cover of this issue is the collaborative team of Anna L. Garden, Sally Brooker and co‐workers at the University of Otago (New Zealand), along with collaborators from Victoria and Montreal (Canada). The image depicts the entropic balancing act between 4 triangles and 3 squares, an argument which must be used with caution. Read the full text of the article at 10.1002/chem.201702153 . Abstract : " The formation of triangles … was very unexpected given the linear (ligand) and right angle (metal) directing geometries of the reaction components. These surprising architectures warrant careful inspection and analysis " Read more about the story behind the cover in the Cover Profile and about the research itself on page 14193 ff. (DOI:10.1002/chem.201702153 ).